(untitled) (Conference Series, 2022)
The Bible covers both personal salvation and important matters of nationality that can impact the life of a believer. According to Scripture, governments derive their power from God and are responsible for maintaining civil order. God is the ultimate source of power and his will supersedes all others. However, because governments are run by individuals with free will, some authorities follow God’s will while others do not. Regardless, all kingdoms and powers are ultimately under God’s supervision and control, and even those that oppose God’s will are serving his purpose. In fact, the early church was able to spread in part due to the persecution it faced from the Roman government. Similarly, the Indonesian government is viewed as having a divine right. As a rising economic power and is expected to become one of the Big Five economies by 2045, Indonesia must prepare to face both opportunities and challenges. Christians have a responsibility to be a blessing to our nation.